Simulation of Cardiovascular and Respiratory Distress for the Pediatric Clerkship - Jody Huber; Michelle Schimelpfenig; Jacqueline Berner; Benson Hsu (Association of American Medical Colleges, 2014)
Abstract This is a high-fidelity simulation reference guide for clinicians teaching inpatient pediatrics to third-year medical students. This guide involves four high-fidelity simulation cases where the students obtain a brief history and physical exam. Through history and physical exam, including recognizing abnormal pediatric vital signs, the students determine a diagnosis and provide initial stabilization. The scenarios include asthma, bronchiolitis, anaphylaxiss, and hypovolemic shock. There is a knowledge test and confidence survey included to evaluate for improvement after the simulation exercises. This module began as a research project involving 80 medical students. Students participated throughout one afternoon of the pediatric clerkship. Students significantly improved their confidence with pediatric patients after the simulation experience. Of a six-question survey, all six questions showed significant improvement in confidence. Many students commented on the quality of education provided by this simulation exercise and requested more simulation in their curriculum. This module is now implemented into the curriculum of the pediatric clerkship and the medical school is improving simulation in other aspects of medical education.